Application of interpersonal psychotherapy for late-life depression in China: A case report - Xu, Hua; Koszycki, Diana (Frontiers in Psychiatry, 2023)
Objectives: Interpersonal psychotherapy (IPT) is an effective treatment for late-life depression, but little is known about its acceptability and efficacy in Chinese patients. This case report describes the use of IPT in a depressed elderly Chinese man. Methods: The patient was a 79-year-old widower who lives alone in a large city in China. This was his first contact with a mental health specialist. His wife died one ago, and his only child lives in the United States with her husband and children. Due to the COVID-19 pandemic, his daughter could not visit him, and his usual social interactions decreased, leaving him feeling isolated, lonely, and depressed. He was diagnosed with a major depressive episode and initially prescribed venlafaxine. However, he failed to show an adequate response to medication and the side effects were intolerable. He was switched to a low dose of Duloxetine (60mg) combined with IPT. Results: The patient’s baseline score on the 17-item Hamilton Depression Rating Scale (HAM-D) was 29, suggesting severe levels of depression. He received 12 sessions of IPT. Role transition was the focus of therapy. Although the patient expressed discomfort in therapy, he developed a good rapport with the therapist and was compliant with treatment. Clinical recovery was achieved at the end of acute IPT treatment (HAM-D score =1). Conclusion: Response to IPT was excellent in this elderly patient, but several points should be noted. First, mental health-related stigma in China can affect treatment engagement. Second, older Chinese are reluctant to speak openly about their personal experiences and feelings. Hence, repeated emphasis on the principles of confidentiality in psychotherapy and forming a strong therapeutic alliance are important. Third, the “empty-nest” household is an emergent phenomenon in China. Helping elderly Chinese navigate changes in traditional Chinese living arrangements and negotiate filial piety with offspring who have moved away are important issues to address in therapy.